(3TQM bUjOI ddTTJQis - (3CMeO Hf eMeO Hf YLjHI GdTQja GdMSfjs ((3GdeQGYTi GdHhYHOdi s)
(3ChdgG (B:s
(3Cda bHd dGejf hgGO bQI GdYjf CNHQfG QViI Gddg Yfg Cf gPG GdGSe GdTQja GdLGeY dSQ s
(3BNQgG (B:s
(3EP GdcdGe UaI GdeJcde heG ajc XgQ Ydi ajc hef dg QZHI heMHI ai gPG Gdaf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdeLGejYs